Iron Oxide/Chitosan Nanocomposite: Properties and Design for AI Enhanced Immunotherapy and Regenerative Medicine - Gizachew Diga (International Journal of Cheminformatics, 2025)
Biopolymers are valuable complex materials. They attract attentions of many scientists, engineers, and medical professionals’ due to their distinguished properties for various applications. In this research, emphasis is given to Fe3O4/Chitosan nanocomposite which has desirable biophysical properties compared to pure Chitosan nanoparticles. Following the green synthesis procedures and characterization methods including thermo gravimetric analysis, AI assisted biomedical application of; Fe3O4/Chitosan nanocomposite is presented. The effect of alkali typically, KOH, in purifying Chitosan during the green synthesis process is presented. Moreover, the effect of Photon energy on biodegradation of Fe3O4/Chitosan nanocomposite in conjunction with varying Fe concentration is discussed in the synthesis procedure. In this regard, AI based approach such as deep learning and machine learning in data generating, analysis, and stimulating biomedical function of Fe3O4/Chitosan composite is seen. It is expected that doping Fe3O4/Chitosan with Fe and GQDs has influence on the properties such biodegradations, biocompatibility, sensitivity, and fluorescence is noticed. AI is also investigated for optimizing the functionality of Fe3O4/Chitosan and predicting the outcome of medical procedures. Moreover, the impact of increasing Fe concentration application of Fe3O4/Chitosan composite in immunotherapy and regenerative medicine is observed. Finally, the possibility of optimizing the biophysical properties of Fe3O4/Chitosan nanocomposite for AI assisted immunotherapy, drug delivery, and regenerative medicine is observed.
Keywords: Biopolymers; Fe3O4/Chitosan nanocomposite; Regenerative medicine; drug delivery; green synthesis; immunotherapy